Challenges with Reference Citations among Postgraduate Students at the Kwame Nkrumah University of Science and Technology, Kumasi, Ghana (Journal of Science and Technology, 2016)
Referencing or citing sources a writer uses is an important part of academic writing. It allows the writer to acknowledge the ideas or words of others used in his/her work and avoid plagiarism. Referencing also demonstrates that the writer has read relevant background literature and can provide authority for statements made. Proper citation allows others to locate the materials used. The researchers’ experience while working on the Kwame Nkrumah University of Science and Technology (KNUST) Institutional Repository brought to the fore challenges postgraduate students encounter in citing references in their academic work. These include poor citing of reference works, inconsistencies in reference citation, use of different citation styles in theses submitted to the repository from the same department among others. Questionnaires and interview methods were employed. Five hundred and six questionnaires were distributed representing ten percent of the total population of postgraduate students of KNUST. Information sought in the questionnaire included students’ biographical data, mode of assessment, departmental referencing format, knowledge of reference style formats, students’ confidence in citing references and faculty’s perception about the way students cited references. This paper seeks to identify and discuss some of the challenges KNUST postgraduate students face in their academic writing. The study found out that KNUST postgraduate students have problems in mastering reference style formats because of the variations in citation. Students tend to rely on books, lecturers or librarians for assistance in ensuring the accuracy of citations they use in their work. Students were not able to identify the citation format they used; they could not cite references for books and journal articles with confidence. Among the recommendations made were that, librarians should play a wider role in the arena of academic integrity, faculty and librarians should collaboratein teaching students about reference citation formats used in academia. College librarians should advocate for the standardization on reference styles in their various colleges. Library orientation given by librarians should be replaced with Information Literacy skills to be offered to students in the first and final years.